2010
DOI: 10.1159/000320119
|View full text |Cite
|
Sign up to set email alerts
|

Affects, Trauma, and Mechanisms of Symptom Formation: A Tribute to John C. Nemiah, MD (1918–2009)

Abstract: John Nemiah was interested in the impact of emotionally traumatic events on mental and bodily processes and in conceptualizing the psychological defenses and deficits that contribute to the development of psychological and somatic symptoms. He viewed dissociation as the central psychological mechanism in the formation of a spectrum of symptoms, and conceptualized alexithymia as a deficit in the cognitive processing of emotion such that stress-induced arousal could bypass the psyche and produce somatic symptoms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 138 publications
0
41
0
3
Order By: Relevance
“…However, the underlying mechanisms for these inflammatory changes may differ and should be explored in future studies. These findings widen the concept of a connection between stress and alexithymia [31,36,37]. …”
Section: Discussionmentioning
confidence: 76%
“…However, the underlying mechanisms for these inflammatory changes may differ and should be explored in future studies. These findings widen the concept of a connection between stress and alexithymia [31,36,37]. …”
Section: Discussionmentioning
confidence: 76%
“…Despite the fact that alexithymia, especially secondary alexithymia, is of clinical importance for the psychiatric and psychotherapeutic approach to cancer patients, the literature on this subject is still very scarce. As noted in a recently published tribute to the work of the co-founder of the concept of alexithymia, John C. Nemiah, the importance of life events in the development of psychological processes intimately related to the formation of psychological or bodily symptoms is widely recognized, but investigating this process has proven to be challenging [47]. A recent study with cancer patients has shown that a multicomponent psychological intervention was able to reduce alexithymia [44], and other studies are currently under way to further evaluate whether psychotherapeutic approaches can influence alexithymia in cancer patients [48].…”
Section: Discussionmentioning
confidence: 99%
“…Skirtingi tyrimai rodo, kad prasta emocijų reguliacija vienaip ar kitaip siejasi su skirtingais psichikos sveikatos sunkumais (3). Be to, manoma, kad psichosomatiniai sunkumai gali būti susiję su prastesniu emocijų supratimu ir emocijų reguliacija (13). Karkhanis ir kolegų (2016) atliktoje apžvalgoje teigiama, kad vaikams ir paaugliams somatiniai sunkumai, kurių negalima paaiškinti medicininėmis priežastimis, dažnai atsiranda dėl sunkumų reiškiant emocijas ir jas reguliuojant (14).…”
Section: Vilniaus Universiteto Medicinos Fakulteto Psichiatrijos Klinikaunclassified